The Ideal Construction of Legal Ownership of Land Rights in the Administrative System of the National Land Agency - Muhammad Ali; Fauzie Yusuf Hasibuan; Idzan Fautanu; Anris Nazaruddin Halim (International Journal of Science and Society, 2022)
Legal certainty as proof of land rights, according to Government Regulation Number 24 of 1997 concerning Land Registration and Government Regulation 18 of 2021 concerning Management Rights, Land Rights, Flats Units, and Land Registration, Legal certainty as proof of land rights is that there is a land registration process that guarantees legal certainty. The method used in this research is descriptive-analytical, with the main approach being normative juridical. Electronic registration, carried out by the Land Office based on Government Regulation Number 18 of 2021, has been very helpful in registering land rights or updating data in the transfer of ownership. However, there are still many obstacles or problems due to human error, such as a lack of Human Resources who are not ready and servers that often experience trouble or difficulties, thus complicating and hindering the land registration process. There must be coordination at all levels in the land registration process at the land office, where the land registration system is crucial for the validity of the documents to avoid overlapping ownership evidence, causing legal uncertainty. The land registration system in Indonesia should adhere to the principle of positive publicity with positive tendencies.